Praktik Baik Pemberdayaan Difabel oleh Kelompok Difabel Desa Makmur Jati Mandiri - Puspita, Damiana Damiana; Astuti, Eka Zuni Lusi (Jurnal Ilmu Kesejahteraan Sosial, 2021)
The participation of people with disabilities is a crucial issue in Indonesia that has emerged along with the development of the concept of social inclusion that encourages the involvement of people with disabilities in social life. Based on the 2015 SUPAS, the most people with disabilities in Indonesia are people who have a little difficulty seeing, which is 5.51%. Meanwhile, the least number of people with disabilities in Indonesia are residents who cannot hear at all, which is 0.09% (Central Bureau of Statistics, 2016). The problems faced by people with disabilities in Indonesia are varied, ranging from limited accessibility in public places, the opportunity to experience discrimination, and the lack of participation of people with disabilities in various activities, including empowerment activities. The Village Difabel Group (KDD) is present as a manifestation of social inclusion for disabled groups. KDD was initiated by SIGAB (Inclusion Center & Difabel Advocacy Movement) as a response to the lack of participation of people with disabilities in village activities. This paper describes the empowerment of people with disabilities by KDD Makmur Jati Mandiri in Jatirejo Village, Lendah District, Kulon Progo Regency, Special Region of Yogyakarta. The data in this study were collected and analyzed using qualitative research methods which were then analyzed using the concept of community empowerment. The empowerment of the disabled by KDD Makmur Jati Mandiri is in the form of providing motivation and skills training. The existence of KDD can encourage people with disabilities to participate in village level activities and organizations.